Fungsi Pantun Adat Perkawinan Melayu Riau (Pantun Function as Malay Marriage Tradition of Riau) - Rezki Puteri Syahrani Nurul Fatimah; Fathiaty Murtadho; Zuriyati Zuriyati (Jurusan Tadris Bahasa Indonesia, 2022)
This study aims to describe the function of rhymes in the marriage customs of the Riau Malay community. The approach used is the sociology of literature. Data were collected through observation, interviews, and documentation. Informants in this study are rhymes at marriage. The results showed that the function of the rhyme in the marriage of the Riau Malay community was (1) as a cultural identity; (2) as a conjunction or tongue; (3) education about culture; (4) as a symbol explanation; and (5) as a guide or procedure. This research has implications for the development of the Indonesian language and literature in universities and schools.Penelitian ini bertujuan untuk mendeskripsikan fungsi pantun pada adat perkawinan masyarakat Melayu Riau. Pendekatan yang digunakan adalah Sosiologi sastra. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Informan dalam penelitian ini adalah tukang pantun pada pernikahan. Hasil penelitian menunjukkan bahwa fungsi pantun pada perkawinan masyarakat Melayu Riau adalah (1) sebagai identitas budaya; (2) sebagai penyambung kata atau lidah; (3) pendidikan tentang budaya; (4) sebagai penjelasan simbol; dan (5) sebagai petunjuk atau tata cara. Penelitian ini dapat diimplikasikan bagi perkembangan ilmu bahasa dan sastra Indonesia di perguruan tinggi maupun di sekolah.